Comparative Analysis of Immunoactivation by Nanosecond Pulsed Electric Fields and PD-1 Blockade in Murine Hepatocellular Carcinoma - Maiweilidan Yimingjiang; Talaiti Tuergan; Xinhua Chen; Hao Wen; Yingmei Shao; RuiQing Zhang; Kasimu Aihaiti; Jing Xue; Tuerganaili Aji; Wei Zhang (Analytical Cellular Pathology)
Nanosecond pulsed electric field (NsPEF) ablation effectively eliminates early-stage hepatocellular carcinoma (HCC) by local ablation and advanced HCC by inducing a remarkable and sustained host immune response. However, this approach is not sufficient to prevent cancer progression, and complementary approaches are necessary for effective immunotherapy. In this study, we evaluated the immunoactivating effects and mechanisms of action of nsPEF ablation and PD-1 blockade on an HCC orthotopic xenograft mouse model. Briefly, 24 C57BL-6J tumor-bearing mice were randomly assigned to three groups: nsPEF ablation group, anti-PD-1 administration group, and untreated control group. Tumor-infiltrating T, B, and NK cell levels and plasma concentrations of Th1 (IL-2, IFN-γ, and TNF-α), Th2 (IL-4, IL-5, IL-6, and IL-10), Th9 (IL-9), and Th17 (IL-17A, IL-17F, IL-21, and IL-22) cytokines were evaluated. Both nsPEF ablation and anti-PD-1 treatment induced immune cell infiltration in local tumors and modulated cytokine levels in the peripheral blood, with distinct changes in the two treatment groups. Based on these findings, both nsPEF ablation and PD-1 antibody administration can trigger a local and systemic immune response in a partially complementary manner, and nsPEF ablation should be considered along with PD-1 blockade for the treatment of HCC.